DESIGNING AN ANDROID-BASED TRADITIONAL CULINARY TOURISM INFORMATION SYSTEM IN THE SI CANGKRING VALLEY, BANYUREJO: PERANCANGAN SISTEM INFORMASI WISATA KULINER JADUL LEMBAH SI CANGKRING BANYUREJO BERBASIS ANDROID - Tita Wuri Prihatiningtyas; Harmastuti Harmastuti; Nuniek Herawati (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2023)
Abstract The Jadul Valley Si Cangkring Market is a new tourist spot located in Jambeyan Padukuhan Banyurejo Tempel Sleman. which offers the concept of a people's market with its characteristics, namely traditional Javanese food in the past. The market is open on Saturday and Sunday mornings as well as on national holidays, affordable food and drink menus, natural tourism potential, culinary delights, and prices offered by SMEs. The potential that exists can be maximized with online promotions, this culinary tour does not yet have online promotion facilities like applications on Android. For this reason, an android-based culinary tourism information system for Jadul Lembah Si Cangkring was created which can be accessed on cellphones called Si Cangkring. In the information system, prospective buyers can see various information related to culinary tourism here. The menu presented in the application, which displays stall information and food menus, a public facilities menu that displays a gallery menu that contains a documentation gallery and a location menu. The results of functional testing with the black box method show that the application can run according to the objectives and expected results. The results of compatibility testing show that the application can run well on a variety of different mobile platforms, different versions of Android from the JellyBean operating system up to a maximum of version 12, different screen sizes and resolutions.